2019
DOI: 10.4103/jispcd.jispcd_435_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of odontogenic maxillary sinusitis with cone beam computed tomography: A retrospective study with review of literature

Abstract: Aim and Objectives: The purpose of this study was to describe the radiographic characteristics of odontogenic maxillary sinusitis as seen on cone beam computed tomography (CBCT) scans and determine whether any tooth or any tooth root, was more frequently associated with this disease. Materials and Methods: The present study included 500 CBCT images that included the entire maxillary sinus of both the sides in all the three planes. The modified classification of Abrahams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 58 publications
2
28
0
3
Order By: Relevance
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only. Figure 1 reports a graphical analysis of the 63 included articles in terms of their overall use of diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-nine studies reported specific diagnostic criteria 7,10,1662 and 14 studies did not report any diagnostic criteria (either original or referenced) for OS. 8,11,6374 It should be noted that four articles 10,21,31,39 were retrospective radiological analyses and provided radiologic diagnostic criteria only. Figure 1 reports a graphical analysis of the 63 included articles in terms of their overall use of diagnostic criteria.…”
Section: Resultsmentioning
confidence: 99%
“…While the clinical examination, both dental and otolaryngological, is straightforward, and the use of nasal endoscopy mandatory, the choice of imaging exams is more complex. Computed tomography (CT) and cone-beam CT (CBCT) are both commonly used for diagnosing sinusitis and identifying the dental problem 17,18 , albeit with different peculiarities (as a general rule, standard CT scan provide a better resolution and contrast for the sinonasal cavities and a better visualization of soft tissues alike, while CBCTs -which represent nevertheless a continuously evolving technology -usually allow for easier diagnosis of dental conditions). However, dental specialists may further require employing techniques such as orthopantomography and periapical radiographs to complete the dental study.…”
Section: Diagnosis Of Odsmentioning
confidence: 99%
“…16 Patients with periapical dental disease can lead to a breach of the Schneiderian membrane resulting in inflammatory mucosal disease and subsequent maxillary sinusitis. 17 Odontogenic sinus disease refractory to treatment with antimicrobial therapy involves definitive treatment of the underlying dental pathology. In such patients, dental extraction of affected tooth root alone may suffice in managing the sinusitis without the requirement of ESS.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 40% of unilateral maxillary sinusitis is odontogenic in origin 16 . Patients with periapical dental disease can lead to a breach of the Schneiderian membrane resulting in inflammatory mucosal disease and subsequent maxillary sinusitis 17 …”
Section: Discussionmentioning
confidence: 99%